2013
DOI: 10.1039/c3ta11603d
|View full text |Cite
|
Sign up to set email alerts
|

Metastable nanostructured metallized fluoropolymer composites for energetics

Abstract: Metastable composites were prepared from a fl uoropolymer-coated nano-aluminum blended formulation entrained in an epoxy matrix. This composition produced a moldable/post-machinable composite that undergoes thermally activated metal-mediated oxidation. The simplistic, scalable design can warrant consideration for a new class of engineered metal-based fl uoropolymer pyrolant composite systems. As featured in:See S. Fluoropolymers have long served as potent oxidizers for metal-based pyrolant designs for the prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 22 publications
1
65
0
Order By: Relevance
“…23 Similar to results shown by Kappagantula et al, 19 the liquid fluorooligomer may readily activate the PIR and promote greater overall Al reactivity. The liquid fluoro-oligomer used in this study is a class of viscous fluorinated oligomers called perfluoropolyethers (PFPEs).…”
Section: ■ Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…23 Similar to results shown by Kappagantula et al, 19 the liquid fluorooligomer may readily activate the PIR and promote greater overall Al reactivity. The liquid fluoro-oligomer used in this study is a class of viscous fluorinated oligomers called perfluoropolyethers (PFPEs).…”
Section: ■ Introductionsupporting
confidence: 70%
“…Miller et al 23 used a PFPE protective coating on nanoscale Al because of its thermal stability at low temperatures (up to 316°C in an oxygen-rich environment) and potential to produce exothermic activity beyond 316°C. 23 When coated with PFPE, the Al particles were able to suspend in a structural epoxy-based matrix. Miller used differential scanning calorimetry (DSC) to study the exothermic behavior for Al−perfluoropolyether (PFPE) blends of various weight percents.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The fuel of choice is Al because of its high relative heat. Moreover, Al and PTFE have an ultrahigh energy density of 21 kJ/cm 3 [27,29]. Second, the reaction of PTFE and Al exhibits a potential gas release because of the low boiling point of reaction product (AlF 3 ) and carbon which would react with oxygen to form oxycarbide in the atmospheric conditions, which is beneficial for the release of energy, combustion rate and many applications [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…In this work, polytetrafluoroethylene (PTFE) and aluminum (Al) are chosen as oxidizer and reducing agent based on the following reasons. First, fluorine is the strongest oxidizing agent, which can be reacted with metal such as Al to form AlF 3 liberating high heat (13.31 kcal/g [26,27]). PTFE contents 76 wt% of fluorine and possesses unique properties, in particular, high chemical and thermal stability [28].…”
Section: Resultsmentioning
confidence: 99%
“…42,43 These analytes were specifically chosen because they provided a range of particle sizes, compositions, surface chemistries, and reactivities. [44][45][46][47] For example, previous studies have shown that protecting agents including organic ligands 40,[48][49][50][51][52][53][54] and polymer [55][56][57] or metal coatings 44,58,59 enhanced reactivity properties and provided chemical control over structural attributes like particle size and monodispersity. The STXM-XAS results were consistent with earlier spectromicroscopy studies, 26,55,60 and also revealed new differences in the surface and micron-scale speciation of Al nanoparticles.…”
Section: Introductionmentioning
confidence: 99%